2014
DOI: 10.1017/s0890060414000213
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary computational synthesis of self-organizing systems

Abstract: A computational approach for the design of self-organizing systems is proposed that employs a genetic algorithm to efficiently explore the vast space of possible configurations of a given system description. To generate the description of the system, a two-field based model is proposed in which agents are assigned parameterized responses to two “fields,” a task field encompassing environmental features and task objects, and a social field arising from agent interactions. The aggregate effect of these two field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The box neighborhood is defined as six regions (Humann et al , 2014; Khani and Jin, 2015), as shown in Figure 11b. The box dynamics are based on the pymunk physics model.…”
Section: Case Study Self-assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…The box neighborhood is defined as six regions (Humann et al , 2014; Khani and Jin, 2015), as shown in Figure 11b. The box dynamics are based on the pymunk physics model.…”
Section: Case Study Self-assemblymentioning
confidence: 99%
“…Through agents’ local interactions, high-level system complexity can be achieved by a bottom-up approach (Reynolds, 1987; Ashby, 1991). Designing complex systems through a self-organizing approach has many advantages, such as adaptability, scalability, and robustness in comparison to traditional engineering systems with centralized controllers (Chiang and Jin, 2012; Humann et al , 2014; Khani and Jin, 2015; Khani et al , 2016; Ji and Jin, 2018). A swarm of robots is often homogeneous, with compact size and limited functionality, and is an example of such SOS (Kennedy, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work on CSO systems has provided useful insights into understanding self-organizing systems and introducing nature-inspired design concepts. A CSO system is based on some key concepts including a dDNA capturing all design information in a bit-string [1], parametric behavioral models for agent control and optimization [36,37], and an FBR mechanism [4].…”
Section: Related Workmentioning
confidence: 99%